The need for psycho-oncological support for melanoma patients: Central role of patients' self-evaluation. Issue 37 (September 2017) - Mayer, Simone; Teufel, Martin; Schaeffeler, Norbert; Keim, Ulrike; Garbe, Claus; Eigentler, Thomas Kurt; Zipfel, Stephan; Forschner, Andrea
Abstract : Abstract: Despite an increasing number of promising treatment options, only a limited number of studies concerning melanoma patients' psycho-oncological distress have been carried out. However, multiple screening tools are in use to assess the need for psycho-oncological support. This study aimed first to identify parameters in melanoma patients that are associated with a higher risk for being psycho-oncologically distressed and second to compare patients' self-evaluation concerning the need for psycho-oncological support with the results of established screening tools. We performed a cross-sectional study including 254 melanoma patients from the Center for Dermatooncology at the University of Tuebingen. The study was performed between June 2010 and February 2013. Several screening instruments were included: the Distress Thermometer (DT), Hospital Anxiety and Depression Scale and the patients' subjective evaluation concerning psycho-oncological support. Binary logistic regression was performed to identify factors that indicate the need for psycho-oncological support. Patients' subjective evaluation concerning the need for psycho-oncological support, female gender, and psychotherapeutic or psychiatric treatment at present or in the past had the highest impact on values above threshold in the DT. The odds ratio of patients' self-evaluation (9.89) was even higher than somatic factors like female gender (1.85), duration of illness (0.99), or increasing age (0.97). Patients' self-evaluation concerning the need for psycho-oncological support indicated a moderate correlation with the results of the screening tools included. In addition to the results obtained by screening tools like the DT, we could demonstrate that patients' self-evaluation is an important instrument to identify patients who need psycho-oncological support.